Models for reaction mechanisms in haemostasis – Contributions from the study of prothrombin activation - Jackson, Craig M. (Thrombosis and Haemostasis, 2007)
A brief history of the development of the contemporary model for the mechanism of prothrombin activation is presented.The focus is on the advances in understanding structure-function relationships in the molecules that comprise “prothrombinase” that occurred primarily during the 1970s. A link between the “classical theory” of hemostasis and the conceptual development of activation complexes as the activators of the precursors of coagulation proteases is developed. It is argued that advances occurred when new ideas arose that could be tested and new technologies enabled more definitive experiments to be performed.
Keywords: Prothrombinase; prothrombin; structure-function; coagulation models; models; history